A fly in the ointment: the re-discovered holotype of ‘Trypeta’ cylindrica Walker, 1853 belongs to the genus Coelopacidia Enderlein (Diptera: Tephritidae), not Chyliza Fallén (Psilidae) - Ross, Andrew J.; Hancock, David L.; Mcalister, Erica; Zhou, Jiale (Zootaxa, 2024)
The ‘type’ of the fly species ‘Trypeta’ cylindrica Walker, 1853, from the William Saunders Collection, was misidentified and subsequently placed in the genus Chyliza Fallén (Psilidae). A specimen from the same collection with identical label data but belonging to Coelopacidia Enderlein (Tephritidae) is hereby identified as the correct holotype and the species should therefore be referred to as Coelopacidia cylindrica (Walker, 1853). Chyliza pallidipes Lamb, 1917 stat. rev. is taken out of synonymy and regarded as the valid name for the species previously treated as ‘Chyliza cylindrica’.